Moral Foundations Theory Among Autistic and Neurotypical Children - Dempsey, Erin Elizabeth; Moore, Chris; Johnson, Shannon A.; Stewart, Sherry H.; Smith, Isabel M. (Frontiers in Psychology, 2022)
Morality can help guide behaviour and facilitate relationships. Although moral judgements by autistic people are similar to neurotypical individuals, many researchers argue that subtle differences signify deficits in autistic individuals. Haidt’s moral foundation theory (2001) describes moral judgements in terms of differences rather than deficits. The current research, aimed at assessing autistic individuals’ moral inclinations using Haidt’s framework, was co-designed with autistic community members. Our aim was to describe autistic moral thinking from a strengths-based perspective while acknowledging differences that may pose interpersonal challenges among autistic youth. We assessed 25 autistic and 23 neurotypical children’s moral judgements using the Moral Foundations Questionnaire for Kids. We used semi-structured interviews and qualitative analysis with a subset of participants to describe children’s moral reasoning. Analyses suggested that autistic and neurotypical children make similar judgements about moral transgressions across all five moral foundations. General linear mixed modeling showed that the greatest predictor of recommending punishment was how bad children deemed moral transgressions to be. We also found a trend that autistic children were more likely to recommend punishment for harmless norms violations than were neurotypical children. Future research could use longitudinal methods to understand the development of moral judgements among autistic and neurotypical children.